Analisis Ubi Jalar Ungu terhadap Kenaikan BB Ibu Hamil KEK - Alhusna, Ise; Rahmadyanti, Rahmadyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of purple sweet potatoes on weight gain in KEK pregnant women at the Keboncau Teluknaga Village Health Center in 2023. The method used is quasi-experimental with a one-group pre-test and post-test research design. The results of the research showed that before LILA was given purple sweet potatoes, the data obtained an average value (mean) of 22.452 cm, a standard deviation value of 0.4976, a minimum LILA size of 21.5 cm, and a maximum LILA size of 23 cm. Before LILA was given purple sweet potatoes, the data obtained an average value (mean) of 23.548 cm, a standard deviation value of 0.5680, a minimum LILA size of 22 cm and a maximum LILA size of 24.5 cm, meaning that the presence of Purple Sweet Potatoes Influences on Increasing the Weight of Pregnant Women in SEZ—Keboncau Teluknaga Village Health Center in 2023 with a p-value of 0.006. Conclusion: after consuming purple sweet potatoes for one month, there was an increase in the average body weight to 42.714 kg or an increase in the average body weight of 0.8857 kg. Keywords: Pregnant Women, KEK, Sweet Potatoes